Two can live as cheaply as one... but three's a crowd - Christopher R. Bollinger; Cheti Nicoletti; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2012)
To measure poverty, incomes must be equivalized across households with different structures. In this paper, we use a very flexible ordered response model to analyze the relationship be- tween income, demographic structure and subjective assessments of financial wellbeing drawn from the 1991-2008 British Household Panel Survey. Our results suggest the existence of large scale economies within marital/cohabiting couples, but substantial diseconomies from the addition of children or further adults. This pattern contrasts sharply with commonly-used equivalence scales, and is consistent with explanations in terms of the capital requirements associated with additions to the core couple.
Keywords: I32; J12; J13; 330; equivalence scales; subjective wellbeing